Wrist pain, distal radial physeal injury, and ulnar variance in young gymnasts: does a relationship exist? - DiFiori, J. P.; Puffer, J. C.; Aish, B.; Dorey, F. (The American Journal of Sports Medicine, 2002)
BACKGROUND: Chronic wrist pain affects up to 79% of young gymnasts. Distal radial growth plate injury and positive ulnar variance have also been reported in this population. HYPOTHESIS: There is a relationship between wrist pain, radiographic findings of distal radial growth plate injury, and ulnar variance in skeletally immature young gymnasts. STUDY DESIGN: Cross-sectional study. METHODS: Fifty-nine gymnasts (28 girls and 31 boys; average age, 9.3 years) completed a questionnaire detailing training and wrist pain symptoms. Each received a wrist examination, grip strength measurement, and bilateral wrist radiographs. RESULTS: Wrist pain was reported by 56% of the gymnasts (33 of 59), with 45% (15 of 33) describing pain of at least 6 months' duration. Factors significantly associated with wrist pain included higher skill level, older age, and more years of training. For those between 10 and 14 years of age, 83% had wrist pain, compared with 44% for those outside of that age range. Fifty-one percent of the gymnasts (30 of 59) had findings of stress injury to the distal radial physis of at least a grade 2; 7% (4) had frank widening of the growth plate. Wrist pain prevalence was significantly related to the grade of radiographic injury. Mean ulnar variance was significantly more positive than established norms. Ulnar variance was not associated with wrist pain or radiographic injury of the distal radial physis. CONCLUSIONS: Radiographic findings of distal radial physeal injury are associated with wrist pain among young nonelite gymnasts.